Impact of Financial Literacy on Risk Tolerance among Young People in Lima using the methodologies of Grable, Potrich, and Mendes - Morales-Gamboa, Manuel Luciano; Flores-Pérez, Alberto (LACCEI, 2025)
Among the young population of Metropolitan Lima, there is a clear tendency to prioritize savings over investment. One possible cause of this predominance is their low tolerance for risk, which leads them to avoid investment decisions. Over time, Peru has improved in terms of financial literacy, as indicated by the results of the Organization for Economic Cooperation and Development (OECD) tests; however, these efforts have not been sufficient to modify this behavior in the younger generations. Therefore, the present research aimed to determine the existence of a relationship between financial literacy and risk tolerance in the Lima population aged 18 to 39, an objective that was successfully achieved by proving a direct relationship between both variables.